(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
The ectomycorrhizal fungal community associated with Pinus Sibirica (Siberian Pine) in a Mongolian forest was investigated in this study. The ectomycorrhizaes were isolated from roots of Siberian pine and identified as Russulia Sardonia, Rhodocollybia butyracea, Tuber borchii, Tricholloma auratum and Lactarius deliciosus. Hartig net, external hyphae and mantle structures of ectomycorrhizae were observed in Siberian pine roots. Journal of agricultural sciences №15 (02): 123-129, 2015